PERFORMANCE ANALYSIS OF INTERSECTION AND NOISE LEVEL AT IR. PH. MOCH. NOOR GURU DANAU INTERSECTION, TANJUNG DISTRICT, TABALONG REGENCY - Ramadhan, Rizki Gilang; Mu’min, Badaruddin (CERUCUK, 2026)
One of the intersections where traffic jams often occur in Tabalong Regency is three-way intersection Ir. Ph. Moch. Noor as known as “guru lake”, this intersection is in a high commercial area where there are shops and religious activities every Tuesday so there are often traffic jams, especially during peak hours in the afternoon.From the research the peak traffic volume occurred between 17.10 – 18.00 WITA. The existing conditions yielded the following results: a Degree of Saturation (Dj) = 1.70 The suboptimal performance of the intersection, an alternative solution involving the implementation of a signalized intersection (TRAFFIC LIGHT) was involving widening of the intersection approach. This alternative produced the following results: Dj = 0.75, with to a LOS grade of B. Additionally, noise levels were recorded at 100.4 dB with correlation 0,571 on the intersection and 96.2 dB with correlation 0,53 in the surrounding area. Keywords: Indonesian Road Capacity Guidelines (PKJI 2023), Simpang Traffic Light, Service Level Index, Capacity, Degree of Saturation, Delay Time, Chance of Queue, Noise Level, and Correlation